Encapsulation of Lactobacillus acidophilus in a pilot‐plant spray‐dryer. Effect of process parameters on cell viability - Slavutsky, Anibal Marcelo; Chavez, Monica C.; Fávaro Trindade, Carmen Sílvia; Bertuzzi, Maria Alejandra (Wiley, 2019)
Encapsulation is a practical technique for the preservation of probiotic cultures. This may be accomplished by spray‐drying, even at large scales. The effect of process parameters such as feed rate and pectin concentration in the feed suspension, on cell viability and stability of encapsulated bacteria was studied. Physical characteristics of the dry powder after the drying process were determined in order to evaluate its influence on product stability and viability during 90 days. The studied parameters showed significant influence on the response variables. Process conditions that generated the highest cell viability after spray‐drying are not the same as the conditions that caused the highest stability and viability after 90 days of storage. Water activity of the dry powder played a fundamental role in the stability of encapsulated bacteria. This indicates the most suitable operating conditions for the production of encapsulated lactic acid cultures in a pilot‐plant spray‐dryer